Outcome of dogs with bone marrow suppression secondary to Sertoli cell tumour. (30th December 2021) - Salyer, Sarah A.; Lapsley, Janis M.; Palm, Carrie A.; Culp, William T. N.; Lundberg, Alycen P.; Phillips, Heidi; McKenna, Charly; Oblak, Michelle L.; Hall, Robyn; Wustefeld‐Janssens, Brandan; Tremolada, Giovanni; Selmic, Laura E.
Abstract: Sertoli cell tumours are one of the most common canine testicular neoplasia. These tumours are significantly more likely to arise in cryptorchid dogs and are often functional, oestrogen‐secreting tumours which can lead to fatal myelotoxicity. The goal of this study was to describe the outcome of dogs with oestrogen‐induced bone marrow suppression secondary to Sertoli cell tumours in seven client‐owned dogs. Medical records from April 1, 2011 through April 1, 2021 were reviewed to identify dogs that underwent surgical management of a Sertoli cell tumour with documented bone marrow suppression. Overall, 5/7 dogs required transfusion of blood products peri‐operatively. Cases 1 and 6 received a transfusion of packed red blood cells (RBC) prior to surgery and case 5 required a transfusion of whole blood. Case 1 also required a transfusion of platelets before surgery. Post‐operatively, cases 1 and 2 received packed RBC's and case 6 received two transfusions of whole blood. Case 3 required transfusions of both fresh frozen plasma and platelets post‐operatively. All dogs survived to discharge and 6/7 dogs had documented improvement in haematopoietic values. Two dogs remained chronically thrombocytopenic. The median hospital stay was 4 days. One dog died within 4 weeks of surgery from worsening pancytopenia. Survival for greater than 1 year was documented in 4/7 dogs, and one dog was lost to follow‐up 4 months post‐operatively. One dog remained severely pancytopenic 4 weeks post‐operatively and received oral lithium treatment. Improvements in all blood cell lines were observed within the 4 weeks and resolution of pancytopenia within 6 weeks. Historically, the prognosis for dogs with bone marrow suppression secondary to Sertoli cell tumours was guarded to poor. This report documented improved outcomes for dogs that underwent surgery, including one dog that received lithium chloride as treatment for Sertoli cell tumour‐induced bone marrow suppression.